(untitled) (International relations and international law Journal, 2018)
This article touches upon the Kazakh language learning deficiencies in Russian schools. In particular, the questions regarding the excessive attention to the grammatical aspect of language learning and the lack of skills training speech. As a result, graduate school and even understand the text in the Kazakh language, it does not have the ability to freely express their thoughts. Subsequently, this negative effect on the further study of a graduate and now a student of a specialized text, words and phrases required syntax. Language – is primarily a mean of communication, so this factor should be the first priority when teaching language. It should be the ability not only to understand the text about their profession, but also have the ability to answer questions, to be able paraphrase the main idea and other ideas presented in the text and be able to express their own vision of any problems. To achieve this goal it is necessary to pay attention to the communication aspect of language learning. And the rest of the problems, such as the ability to competently and correctly express their thoughts in writing is necessary to move only after the first goal, i.e. the use of language communication. Key words: text, word combinations, language issues, communicative skills, development of oral speech.